The Co-relationship between Inter-gang conflicts for longitudinal expansion and retain their identification in an urban context - Wijewardhana, B.V.N. (International Journal of Humanities and Social Science Research, 2017)
ln the urban city many gangs are there and there are inter-gang rivalry. They are established in GN divisions and one gang tries to run-over the other. This paper try to reveal why is this? How has they converted conflict into a privilege for their survival? How gangsters have become heroes and how people look up to them? In anti-social activities popular gangs are looked up to for support? The Research focused on 493 identified youth gang members belonging to 75 gangs within 14 GN divisions in Colombo city, within the age group of 18 - 32 years. All the said gangs and the gang members were identified within the study area through a snowball technique using available contacts and via the data gathered using formal research methods. As a whole, appropriately followed localization method is a crucial factor for a gang to perform in a planned and secured manner. Basically, a sufficient time margin might be necessary for a gang to be established in a geographical area. As an average, it needs minimum 5 years of duration to attain such stability. Another important matter is that any new group or gang cannot be formally established in a particular area without permission or acceptance of established gangs in the targeted area.
Keywords: Co-relationship, Inter-gang Conflicts, Identification, Longitudinal Expansion, Urban context